STUDIES ON THE METABOLISM OF SHIGELLA IV. 3: Nutritional Requirements of Shigella Flexneri Serotype - Pan, Sylvia F. (1962)
Pan, Sylvia F. (University of Pittsburgh, Pittsburgh, Pa.), Robert B. Yee, and Horace M. Gezon. Studies on the metabolism of Shigella. IV. Nutritional requirements of Shigella flexneri serotype 3. J. Bacteriol. 83:61–65. 1962.—A study of the nutritional requirements of five strains of Shigella flexneri serotype 3 was carried out. Four of the strains could be cultured in a synthetic medium composed of a mineral salts glucose base, NH(4)H(2)PO(4) or an amino acid as the nitrogen source, and nicotinamide; the fifth one required the presence of both NH(4)H(2)PO(4) and an amino acid in the medium. Variation among the former strains in their nitrogen and vitamin requirements was observed. The least fastidious one produced maximal growth using the simple ammonium salt as its source of nitrogen and did not require the addition of nicotinamide. Two strains were moderately fastidious, producing better growth within 24 hr in the presence of l-aspartic acid instead of NH(4)H(2)PO(4), and requiring nicotinamide as an accessory growth factor. The fourth strain was extremely fastidious, growing poorly or not at all in the synthetic medium. Incubation of large inocula of the fastidious strain in synthetic medium and over a prolonged period resulted in adaptation of the organism to the medium. Some of the adapted cultures grew readily in the presence of NH(4)H(2)PO(4) and did not require nicotinamide.